On Carbon Tax Effectiveness in Inducing a Clean Technology Transition: An Evaluation Based on Optimal Strategic Capacity Planning - Wolf, Nathalia; Escalona, Pablo; López-Campos, Mónica; Angulo, Alejandro; Weston, Jorge (Sustainability, 2023)
This paper studies carbon tax effectiveness in inducing a transition to cleaner production when a firm faces different technologies and demands over a planning horizon. To determine carbon tax effectiveness, we propose a model based on strategic capacity production planning under carbon taxes that considers proper performance measures. The model, which is formulated as a mixed integer linear problem (MILP), considers issues that previous works have not studied jointly, and that are relevant in a technological transition, such as machine replacement, workforce planning, and maintenance. The effectiveness measures consider levels of clean production and periods to reach a technological transition. Our computational experiments, based on a real case, have shown that in the absence of carbon taxes, a firm has no incentive to transition to clean technology. Still, the effectiveness of carbon taxes depends on the characteristics of the technology available for the production process and the magnitude of the demand. We include managerial insights aimed at both companies and the environmental authority.
CRIS-Team Scopus Importer:2023-08-25
Keywords: carbon tax effectiveness; clean technology transition; MILP; strategic capacity planning